Peranan Dewan Pengawas Syariah Dalam Pembiayaan Mudarabah Pada Pt. Bprs Gebu Prima - Miftahul Isror; Rahmayati Rahmayati (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
Apart from the establishment of Islamic banks in Indonesia, private banks also follow sharia principles, including PT. BPRS (Islamic People's Credit Bank) Gebu Prima. PT. BPRS Gebu Prima is one of the Rural Banks (BPR) in the city of Medan. BPR is a bank that serves business activities conventionally or based on sharia principles which in its activities does not provide services in payment traffic. BPR Syariah Gebu Prima. PT offers services for saving time deposits or savings, credit and loans, financing and placement of funds based on sharia principles. Immediately visit the nearest Rural Bank (BPR) on opening days and hours. You can also contact the telephone contact for other information. The increase in Islamic banking and BPR in Indonesia or more precisely in Medan, North Sumatra, cannot be separated from the Sharia Supervisory Board. The Sharia Supervisory Board is an extension of the National Sharia Council (DSN) to straighten transactions carried out. With good supervision, forms of application of sharia products will be created that have been determined by the National Sharia Council.